A review of the clam shrimp family Leptestheriidae (Crustacea: Branchiopoda: Spinicaudata) from Venezuela, with descriptions of two new species - Garcia, Jose Vicente; Pereira, Guido (Zootaxa, 2003)
The clam shrimps of the family Leptestheriidae from Venezuela are reviewed. Leptestheria venezuelica Daday, 1923, and two new species (L. cristata n. sp. and L. brevispina n. sp.) are presented. A redescription of L. venezuelica, descriptions of the new species, and comparisons with other South American species are included. A checklist of world Leptestheriiidae is included.